(3GdMeGjI GdbGfhfjI dYed GdGWaGd ai GdbGfhf GdeUQi GdebGQf (B/ s - (3QGfjG YHOGdefYe YHOGdMejOs; (3eMeO GMeO GSeGYjds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3jSJNdU ehVhY gPg GdQSGdI ai OQGSI GdMeGjI GdbGfhfjI dYed GdGWaGd ai GdbGfhf GdeUQi GdebGQf (B: (3MjK JWQafG ef NdGd gPg GdQSGdI Gdi GdJWhQ GdJGQjNi ddCMcGe GdbGfhfjI dYed GdGWaGd hMLe GdXGgQI Ydi GdeSJhi GdYGdei hGdYQHi hGdhWfi(B.(3ceG QcRfG Ydi GdGSHGH GdeDOjI dYed GdGWaGd ShGA GdGSHGH GdQFjSjI Gh GdKGfhjI hHMKfG GdGKGQ GdeJQJHI Ydi Yed GdGWaGds
(3jTJed Ydi GdedGMb(B: (3UaMGJ (B233-240s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B241-255s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdMO GdGOfi dSf GdYeds; (3XGgQI Yed GdGWaGds; (3eYGjjQ GdYed GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs